Assessing Employee Performance Based on Human Resource Quality and Technology Utilization - Yani Ekowati; Muhammad Firdaus; Hary Sulaksono (Innovation Business Management and Accounting Journal, 2024)
The purpose of this study is to test and analyze the influence of human resource quality and information technology on employee performance. This study uses a quantitative approach with a sample of 44 people from Curahdami District employees, Bondowoso Regency, East Java. The results of the study indicate that the quality of human resources has a significant effect on employee performance, the use of technology also has a significant effect on employee performance. The implications of this study indicate that improving the quality of human resources can directly improve employee performance, so organizations need to focus on training and developing employee competencies. In addition, effective use of information technology also plays an important role in increasing productivity, so investment in technology infrastructure is very important. Thus, public organizations at the sub-district level must consider the integration between human resource development and the application of information technology to achieve optimal performance.